(untitled) (Hekima Review, 2014)
Though there is no concept of democracy as such in Black African Tradition, its reality, however, is present. In fact, long before the arrival of the colonial people, the Africans had their own political forms, administrative and socio-economic systems which wereefficient for their daily life. Yes, we can say that Africans were a happy people and did not feel oppressed. The authority of the chief or king, absolute as it might have been, was not unlimited, as Ki-Zerbo observes among the Mossi of Burkina-Faso.1 Our contributionshall therefore try to point out in concrete terms how possible it was in the African tradition to live a political life comparable to modern democracy and that even went beyond the latter. To reach there, it is imperative to discuss the role played by the eldersof a community and the importance of the so-called palaver institution for the harmony in a communal life.